2023
DOI: 10.1093/hr/uhad222
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate deficiency induced by infection promotes synthesis of anthracnose-resistant anthocyanin-3-O-galactoside phytoalexins in the Camellia sinensis plant

Tongtong Li,
Shenrong Wang,
Dandan Shi
et al.

Abstract: Tea (Camellia sinensis) is a well-known beverage crop rich in polyphenols with health benefits for humans. Understanding how tea polyphenols participate in plant resistance is beneficial to breeding resistant varieties and uncovering the resistance mechanisms. Here, we report that a Colletotrichum infection-induced ‘pink ring’ symptom appeared outside the lesion, which is highly likely to occur in resistant cultivars. By identifying morphological feature-specific metabolites in the pink ring and their associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Our previous research has shown that the infection of Colletotrichum can induce the accumulation of anthocyanins in tea leaves [ 28 ]. In this study, we utilized this experimental system to investigate the impact of overexpressing the CsWD40 3D , CsWD40 3A , and CsMPK4a gene on anthocyanin biosynthesis in tea leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research has shown that the infection of Colletotrichum can induce the accumulation of anthocyanins in tea leaves [ 28 ]. In this study, we utilized this experimental system to investigate the impact of overexpressing the CsWD40 3D , CsWD40 3A , and CsMPK4a gene on anthocyanin biosynthesis in tea leaves.…”
Section: Resultsmentioning
confidence: 99%